Policy mechanisms to reduce bubble tea consumption among youths in Singapore - Lee, Aaron Hui Kiat (Nanyang Technological University, 2021)
It is commonly known that the consumption of Sugar-Sweetened Beverages (SSB) increases an individual’s risk of developing diabetes. Consumption of bubble tea, a SSB with very high sugar and calorie content, is popular among Singaporeans. Yet, there is still minimal research on the issue of bubble tea and mechanisms to reduce its consumption in Singapore. Our research aims to address this research gap. We conducted a survey by recruiting university students in Singapore to explore policy mechanisms which reduce their bubble tea consumption. University students are a good proxy for the youth population in Singapore as they fall within the age range of youths. Participants were randomly assigned to three groups - Control Group, Front of Package Labelling (FOP) Health Group and Taxation Group - to test their response to various policy measures. We used a difference-in-differences model and ran several regressions to generate our results. From our research, we found that in certain subgroups, for instance those who lived in HDB flats or choose bubble tea with 0 to 25% of sugar, participants reduced their bubble tea consumption when faced with the taxation effect. Meanwhile, FOP health treatment did not yield any statistically significant results to suggest its effectiveness in reducing bubble tea consumption. This study contributes to the literature in suggesting that tax on bubble tea is more effective than FOP health effect in addressing the growing problem of bubble tea consumption among youths in Singapore.